2023
DOI: 10.3390/nu15041021
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Rejection and Overinclusion in Eating Disorders: An Experimental Investigation of the Impact on Emotions, Stress Perception, and Food Attitudes

Abstract: (1) Background: the investigation of how interpersonal functioning affects eating psychopathology has been receiving increasing attention in the last decade. This study evaluates the impact of virtual social inclusion or ostracism on emotions, perceived stress, eating psychopathology, and the drive to binge or restrict in patients across the eating disorder spectrum. (2) Methods: a group of 122 adolescent and adult females with different eating disorder diagnoses were compared to 50 healthy peers with regards … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 87 publications
(114 reference statements)
1
1
0
Order By: Relevance
“…Indeed, research supports the role of positive social engagement in the improvement of weight outcomes among adults ( 84 ), children ( 85 ), and adolescents ( 86 , 87 ). A recent study demonstrated that thoughts about binge eating reduced following an interpersonal scenario characterized by social inclusion in a Cyberball task among individuals with BED ( 88 ), which aligns with current findings linking positive social cues and lower palatable food intake. Engagement of the dlPFC, which supports cognitive control processes, powerfully modulates engagement of the ventral stream, a series of brain regions beginning in the occipital cortex that represents the identity of objects.…”
Section: Discussionsupporting
confidence: 88%
“…Indeed, research supports the role of positive social engagement in the improvement of weight outcomes among adults ( 84 ), children ( 85 ), and adolescents ( 86 , 87 ). A recent study demonstrated that thoughts about binge eating reduced following an interpersonal scenario characterized by social inclusion in a Cyberball task among individuals with BED ( 88 ), which aligns with current findings linking positive social cues and lower palatable food intake. Engagement of the dlPFC, which supports cognitive control processes, powerfully modulates engagement of the ventral stream, a series of brain regions beginning in the occipital cortex that represents the identity of objects.…”
Section: Discussionsupporting
confidence: 88%
“…As a proof of this, patients recalled social difficulties as preceding their ED and worsening after illness onset [ 26 ]. Experimental studies have demonstrated heightened sensitivity to social stress [ 27 , 28 ] and attentional bias towards social rejection [ 29 ] in individuals with EDs and interpersonal difficulties have been shown to predict treatment outcome [ 30 ].…”
Section: Introductionmentioning
confidence: 99%